2020
DOI: 10.3390/ma13071695
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Platelet-Rich Fibrin on Hard Tissue Healing: A Histomorphometric Crossover Trial in Sheep

Abstract: Bone defects lead to aesthetic and functional losses, causing dental rehabilitation to be more difficult. The objective of this work is to histologically assess the hard tissue healing of bone defects filled with platelet-rich fibrin (PRF) alone or as an adjuvant for mixing with and covering anorganic bovine bone (ABB), compared to ABB covered with a resorbable collagen membrane (CM). This study was designed as a crossover animal study. Four 5-mm tibia defects, 5 mm apart from each other, were surgically creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In addition, To, Su, Hidaka, Okudera and Matsuo [37] also showed superior bone formation in dogs sockets lled with A-PRF membrane (200g for 8 min) in comparison to the blood clot. However, other pre-clinical studies reported no additional effect of standard membrane PRF in critical defects bone formation [36,38,39,41].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, To, Su, Hidaka, Okudera and Matsuo [37] also showed superior bone formation in dogs sockets lled with A-PRF membrane (200g for 8 min) in comparison to the blood clot. However, other pre-clinical studies reported no additional effect of standard membrane PRF in critical defects bone formation [36,38,39,41].…”
Section: Discussionmentioning
confidence: 98%
“…The addition of bioactive materials has been extensively proposed to improve the osteoinductive properties of the DBBM graft [35, 36, 38-41, 51, 52]. Studies evaluating the DBBM graft mixed with PRF membrane obtained by standard protocol showed superior bone formation in comparison to DBBM or PRF alone in calvaria [35], tibia [39], and femur [52] bone defects. However, other studies in calvaria [36,40,41,51] or tibia [38] defects reported that DBBM mixed with PRF did not provide any additional effect on bone formation in comparison to DBBM alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histomorphometry is well suited for preclinical animal models that can provide substantial histological information and evaluate standardized groups [ 21 ]. In this study, sheep were used as experimental animals due to them being frequently used models in dental studies to evaluate bone healing, having a bone structure and remodeling that are similar to those of human beings, and having proper structure for wide defects [ 22 , 23 , 24 ]. Using the sheep’s right ilium as the control group and left ilium as the experimental group made it possible to host both groups on the same animal.…”
Section: Discussionmentioning
confidence: 99%